2023
DOI: 10.1039/d3sc00090g
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme-powered microRNA discriminator for the subtype-specific diagnosis of breast cancer

Abstract: This paper reports an enzyme-powered microRNA discriminator to selectively distinguish breast cancer cells from normal cells and further identify subtype-specific features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…However, this method is time‐consuming and exhibits limits of detection at the sub‐pM level. Alternatively, Zhao's group [26] reported enzyme‐assisted DNA signal amplification for cancer subtyping based on an electrochemical technique (Figure 2b). The miRNA discriminator was involved in two TMSD reactions, in which two miRNA biomarkers (miR21 and miR210) initiated strand displacement sequentially and a T7 exonuclease (EXO) powered digestion procedure.…”
Section: Cellular Biomarker For Differentiating Subtypes Of Cancer Ba...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, this method is time‐consuming and exhibits limits of detection at the sub‐pM level. Alternatively, Zhao's group [26] reported enzyme‐assisted DNA signal amplification for cancer subtyping based on an electrochemical technique (Figure 2b). The miRNA discriminator was involved in two TMSD reactions, in which two miRNA biomarkers (miR21 and miR210) initiated strand displacement sequentially and a T7 exonuclease (EXO) powered digestion procedure.…”
Section: Cellular Biomarker For Differentiating Subtypes Of Cancer Ba...mentioning
confidence: 99%
“…(a) MALDI-MS for simultaneously detecting multiple miRNA biomarkers from the subtypes of different breast cancers [25]. (b) Enzyme-driven miRNA detection with the electrochemical measurement in the subtype profiling of breast cancer cells [26]. Graph copyright from reference[25,26] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive investigations have consistently demonstrated that miRNAs hold great potential to serve as vigorous biomarkers for cancer diagnosis. [4][5][6] Various strategies have been reported for the detection of miRNAs in vitro and within living cells. [7][8][9] However, it is important to acknowledge that there is usually a variety of miRNAs with abnormal expression in a particular cancer, and the dysregulation of a single miRNA may be related to multiple cancers.…”
mentioning
confidence: 99%
“…Extensive investigations have consistently demonstrated that miRNAs hold great potential to serve as vigorous biomarkers for cancer diagnosis. 4–6…”
mentioning
confidence: 99%